Hubungan Asupan Serat dengan Kadar Kolesterol Total pada Pria dan Wanita Dewasa di Posbindu Purwobakti Husada Kota Surakarta - Rizma, Amalina; , Zulia Setiyaningrum, S.Gz, M.Gizi (2017)
High cholesterol may increase the risk of cardiovascular disease. Fiber intake affect total cholesterol levels by preventing the absorption of fats and binding bile acid which is the final product of cholesterol.The aim of this study was to determine the relationship between fiber intake and total cholesterol levels on men and women at Posbindu Purwobakti Husada Surakarta. The research was an servasional study with cross sectional approach. Thirthy-six adults respondents were recruited using Purposive Sampling technique. The data of fiber intake were obtained using semi-quantitative Food Frequency Questionnaire and total cholesterol levels were analyzed by spectrophotometer using venous blood. The relationship between fiber intake with total cholesterol levels were analyzed using Rank Spearman test.72.2% respondents have very less fiber intake and 50% respondents have borderline high total cholesterol level. The results of statistic analysis showed that there was no relationship between fiber intake and total cholesterol levels with p-value 0.131.There was no relationship between fiber intake and total cholesterol levels on men and women at Posbindu Purwobakti Husada Surakarta.